Community mediation in Malaysia: the challenges faced by community mediators and the DNUI - Abdul Hak, Nora; Ambaras Khan, Hanna; Mohamad, Akmal (UPM Press, 2015)
The Department of National Unity and Integration (DNUI) designed community mediation programme to provide mediation as a method of dispute resolution to be adopted at community level. The Department trained “Ahli Jawatankuasa Rukun Tetangga” (Peaceful Neighbourhood Committees) to be the community mediator. The objective of this paper is study the challenges facing by the community mediators and the Department in practising and providing mediation services to the community, respectively. In writing this paper, qualitative research method was adopted by the authors in gathering data. From the data collected, it is found that community mediation programme is very new, the mediators are yet to be recognised, there is lack promotion and support from Rukun Tetangga committees and limited funds allocated for the programme. It is suggested that the community mediation programme in Malaysia to have a proper centre and structure as to ensure that the programme is handled by an appropriate body that will overcome all challenges and subsequently, allows the programme to be successful and benefited Malaysians.